Hydroxyapatite nanoparticles-cell interaction: new approaches to disclose the fate of membrane-bound and internalised nanoparticles - Bonany, Mar (2023)
Hydroxyapatite nanoparticles are popular tools in bone regeneration, but they have also been used for gene delivery and as anticancer drugs. Understanding their mechanism of action, particularly for the latter application, is crucial to predict their toxicity. To this end, we aimed to elucidate the importance of nanoparticle membrane interactions in the cytotoxicity of MG-63 cells using two different types of nanoparticles. In addition, conventional techniques for studying nanoparticle internalisation were evaluated and compared with newer and less exploited approaches. Hydroxyapatite and magnesium-doped hydroxyapatite nanoparticles were used as suspensions or compacted as specular discs. Comparison between cells seeded on the discs and those supplemented with the nanoparticles allowed direct interaction of the cell membrane with the material to be ruled out as the main mechanism of toxicity. In addition, standard techniques such as flow cytometry were inconclusive when used to assess nanoparticles toxicity. Interestingly, the use of intracellular calcium fluorescent probes revealed the presence of a high number of calcium-rich vesicles after nanoparticle supplementation in cell culture. These structures could not be detected by transmission electron microscopy due to their liquid content. However, by using cryo-soft X-ray imaging, which was used to visualise the cellular ultrastructure without further treatment other than vitrification and to quantify the linear absorption coefficient of each organelle, it was possible to identify them as multivesicular bodies, potentially acting as calcium stores. In the study, an advanced state of degradation of the hydroxyapatite and magnesium-doped hydroxyapatite nanoparticles within MG-63 cells was observed. Overall, we demonstrate that the combination of fluorescent calcium probes together with cryo-SXT is an excellent approach to investigate intracellular calcium, especially when found in its soluble form.